Comparative Analysis of B-Cell Receptor Repertoires Induced by Live Yellow Fever Vaccine in Young and Middle-Age Donors - Davydov, Alexey N.; Obraztsova, Anna S.; Lebedin, Mikhail Y.; Turchaninova, Maria A.; Staroverov, Dmitriy B.; Merzlyak, Ekaterina M.; Sharonov, George V.; Kladova, Olga; Shugay, Mikhail; Britanova, Olga V.; Chudakov, Dmitriy M. (Frontiers in Immunology, 2018)
Age-related changes can significantly alter the state of adaptive immune system and often lead to attenuated response to novel pathogens and vaccination. In present study we employed 5’RACE UMI-based full length and nearly error-free immunoglobulin profiling to compare plasma cell antibody repertoires in young (19-26 years) and middle-age (45-58 years) individuals vaccinated with a live yellow fever vaccine, modelling a newly encountered pathogen. Our analysis has revealed age-related differences in the responding antibody repertoire ranging from distinct IGH CDR3 repertoire properties to differences in somatic hypermutation intensity and efficiency and antibody lineage tree structure. Overall, our findings suggest that younger individuals respond with a more diverse antibody repertoire and employ a more efficient somatic hypermutation process than elder individuals in response to a newly encountered pathogen.